2005
DOI: 10.1007/s10209-003-0084-4
|View full text |Cite
|
Sign up to set email alerts
|

Senior users of the internet: lessons from the cybernun study

Abstract: This paper presents a study that examined computer use and life satisfaction of senior religious sisters. A sample was obtained of 103 nuns in Upstate New York. Participants self-identified as computer users (CU) or non-users (NU), completed demographic information, the life satisfaction index-Z (LSIZ), the attitudes toward computer use scale (ATCUS), and responded to additional semi-structured questions. No statistically significant differences were found between CU and NU in life satisfaction. A cross-compar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2009
2009
2012
2012

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…In [47] it was found that small font sizes, confusing advertisements and the standard mouse were accessibility barriers for nuns to go online. This study was based on a survey measuring life satisfaction and attitudes towards computer use.…”
Section: Related Workmentioning
confidence: 98%
“…In [47] it was found that small font sizes, confusing advertisements and the standard mouse were accessibility barriers for nuns to go online. This study was based on a survey measuring life satisfaction and attitudes towards computer use.…”
Section: Related Workmentioning
confidence: 98%
“…Age-related changes in manual dexterity had a negative impact on web browsing with several input devices [38]. Small font sizes, confusing advertisements and the standard mouse were relevant barriers for nuns [64]. Scrolling, opening new windows in the browser, the small size of buttons and the short distance between navigation buttons were accessibility barriers for disabled and older users [27,34].…”
Section: Introductionmentioning
confidence: 99%